2021
DOI: 10.1080/13670050.2021.1910621
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic consequences of toing and froing: factors that modulate narrative development in bilingual returnee children

Abstract: This longitudinal study examined the development of narrative micro-and macrostructure in Japanese-English bilingual returnee children. Returnees are children of immigrant families who move to a foreign country, spending a significant portion of their formative developmental years in the foreign majority language context before returning to their native language environment. The returnees did a narrative task in both their L1 (Japanese) and L2 (English) immediately upon their return to their native language en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
(81 reference statements)
0
10
0
Order By: Relevance
“… Charest et al (2020) pronounced TTR “disfavored for clinical use” (p. 1868) and not worthy of research investigation. Thus, it is dispiriting to note its frequent use in clinical practice ( Finestack and Satterlund, 2018 ), in texts that educate clinicians in training, and even recent research articles examining measurement of expressive child language skills ( Gonzalez Villasanti et al, 2020 ; Manning et al, 2020 ; Kubota et al, 2021 ; Arjmandi et al, 2022 ). In this study, across more than 1500 conversational language samples from children ages 2 to 6 years of age, TTR was worse than uninformative: if used to make clinical decisions, it would have identified numerous children with known impairment as typically functioning, while identifying otherwise typical children as deficient in expressive lexical diversity during conversation.…”
Section: Discussionmentioning
confidence: 99%
“… Charest et al (2020) pronounced TTR “disfavored for clinical use” (p. 1868) and not worthy of research investigation. Thus, it is dispiriting to note its frequent use in clinical practice ( Finestack and Satterlund, 2018 ), in texts that educate clinicians in training, and even recent research articles examining measurement of expressive child language skills ( Gonzalez Villasanti et al, 2020 ; Manning et al, 2020 ; Kubota et al, 2021 ; Arjmandi et al, 2022 ). In this study, across more than 1500 conversational language samples from children ages 2 to 6 years of age, TTR was worse than uninformative: if used to make clinical decisions, it would have identified numerous children with known impairment as typically functioning, while identifying otherwise typical children as deficient in expressive lexical diversity during conversation.…”
Section: Discussionmentioning
confidence: 99%
“…As emphasized by Reinders (2017), multiplayer online role-playing games "create many opportunities for collaboration and competition and rich opportunities for exposure to L2 input as well as opportunities for L2 output and interaction" (p. 332). The study contributes to the field and discusses how the available technology allowed the returnee to continue to receive abundant L2 input, use the L2 daily, and interact with native speakers after returning home and how that aligns with recent findings on the significance of continued L2 input post-return (e.g., Huensch et al, 2019;Kubota et al, 2020Kubota et al, , 2021.…”
Section: Introductionmentioning
confidence: 53%
“…Researchers have recognized the continued L2 input post-return (Slavkov, 2015) and active bilingualism (Kubota et al, 2020) in the L2 environment as major factors in L2 maintenance and improvement. For instance, Kubota et al (2021) found that returnees who continued to receive L2 input better maintained their English microstructure after being re-immersed in the L1 environment. Slavkov (2015) declares that "continued input in a language that has become passive can be beneficial" (p. 715).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting evidence comes, mainly, from studies on Turkish returnees, who moved (back) to Turkey from Germany (Antonova-Unlu et al, 2021;Daller, 1999;Daller & Yıldız, 1995;Kaya-Soykan et al, 2020;Treffers-Daller et al, 2007;. Research on other "reactivated" HLs is still residual (see Rato, 2016, on global accent, andKubota et al, 2021, on the narrative abilities of children who returned to Japan from an English-speaking country).…”
Section: Measuring Language Dominancementioning
confidence: 99%